2014
DOI: 10.3389/fneur.2014.00222
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pre-Spike Network in Patients with Mesial Temporal Lobe Epilepsy

Abstract: Background: Seizures and interictal spikes in mesial temporal lobe epilepsy (MTLE) affect a network of brain regions rather than a single epileptic focus. Simultaneous electroencephalography and functional magnetic resonance imaging (EEG-fMRI) studies have demonstrated a functional network in which hemodynamic changes are time-locked to spikes. However, whether this reflects the propagation of neuronal activity from a focus, or conversely the activation of a network linked to spike generation remains unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…Previous studies have shown that changes in synchronization of oscillatory brain activity occurs prior to IED onset (Keller et al, 2010;Faizo et al, 2014;Bourel-Ponchel et al, 2017). However, it has not been clear whether these pre-IED oscillations exhibit a dynamical evolution, with increasing synchronization in the irritative zone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that changes in synchronization of oscillatory brain activity occurs prior to IED onset (Keller et al, 2010;Faizo et al, 2014;Bourel-Ponchel et al, 2017). However, it has not been clear whether these pre-IED oscillations exhibit a dynamical evolution, with increasing synchronization in the irritative zone.…”
Section: Resultsmentioning
confidence: 99%
“…In support of this view, several computational and animal models have demonstrated that IEDs and their cellular correlate, the paroxysmal depolarizing shift, can be triggered to occur momentously by increasing the excitation/inhibition ratio (Ayala et al, 1970;Schwartzkroin and Prince, 1979;Voskuyl and Albus, 1985;Mccormick and Contreras, 2001). However, analysis of human IED generation demonstrate that that there are additional changes in the brain state prior to IED onset, indicating that the context surrounding IED events develop over a longer time scale (Keller et al, 2010;Faizo et al, 2014;Bourel-Ponchel et al, 2017). Hemodynamical activation, for instance, peak one second before IEDs occur (Hawco et al, 2007;Jacobs et al, 2009;Rathakrishnan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effects of IEDs on cognitive networks were not often explored until recently. Following pioneering work relating IED-correlated decreases in Default Mode Network activity in temporal lobe epilepsy (84) and generalized epilepsy (85), recent works have shown the possible impact of interictal activity on several ICNs in focal epilepsy in adults (33, 36, 45), focal epilepsy in children (22), children with idiopathic focal epilepsy [Benign Epilepsy with Centro-temporal Spikes (BECTS)] (53, 55, 86), epileptic encephalopathy (5659), as well as generalized epilepsies (61, 64), including Childhood Absence Epilepsy (CAE) (87), and even reflex epilepsies (60). The majority of recent EEG-fMRI studies who evaluate the interaction between interictal discharges, ICNs, and their relationship to neuropsychological outcome have been in BECTS patients; these studies found a negative correlation between cognitive functioning and Functional Connectivity (FC).…”
Section: Methodsmentioning
confidence: 99%
“…Independently of Lopes et al, Faizo et al recently studied functional connectivity between hippocampi immediately prior to IEDs in a group of 15 mesial TLE patients ( 20 ). They observed functional connectivity decrease prior to the IED onset.…”
mentioning
confidence: 99%